Pluralities without reified Wholes : a phenomenological response to Hans Berhard Schmid’s collectivism - Chelstrom, Eric (Investigaciones Fenomenológicas, 2011)
Collective intentions form the basis of the social world and represent a mode of experience overlooked in some phenomenological analysis: weintentionality. Some argue that the subject of intentionality is the intending subject, but phenomenology is committed to intentionality in essence being something restricted to individual subjectivities. The intending subject, the conscious subject, is not equivalent to the subject of intention or subject matter of acts of consciousness, i. e. it is not the syntactical subject referenced in and through an intentional act. Hans Bernhard Schmid disagrees; here I present the case for subjective individualism with respect to collective intentionality and respond to his arguments for collectivism.